Efficiency and Financial Sustainability of Microfinance Institutions: A Study of Jaffna District - Velnampy, T.; Ajanthan, A. (My University, 2013)
Microfinance is the provision of thrift, saving, credit and financial services and products of very small amount to the poor in rural, semi-urban and urban areas for enabling them to raise their income levels and improve their standard of living. (Sen., 2008). In numerous studies done across the world, it is generally believed that various microfinance initiatives have been able to make a difference in the target populations lives. However, increasing doubts have been raised over the financial sustainability of microfinance institutions. MFIs need to be economically viable and sustainable in the long run but economic implications of long term sustainability are not being considered (Srinivasan et al., 2006). Microfinance collectively refers to the supply of loans, savings accounts, and other basic financial services like insurance, to the poor. About one billion people globally live in households with per capita incomes of one dollar per day (Morduch J. 1999). Microfinance Institutions (MFIs) are special financial institutions. They have both a social nature and a for-profit nature. Their performance has been traditionally measured by means of financial ratios. The context of the study is to analyze the prospects of micro finance industry in Jaffna District special reference to MPCS Co-operative Rural Bank. This study examines the relationship between efficiency of co-operative rural banks with its financial sustainability. The objective of the study is to evaluate efficiency and financial sustainability of microfinance institution in relates with its rate of interest, operating revenue, administration & operating expenditure, administrative, operating, and financial and staff efficiency.10 rural banks were selected in Jaffna district using stratified random sampling method. Research hypothesis were formulated that there is an impact of efficiencies on financial sustainability and operational and financial efficiencies are significant impact in determining the financial sustainability. Ratio analysis was used to evaluate the efficiencies of the rural banks.
Keywords: Micro finance Institutions; Efficiency; Financial Sustainability